2021
DOI: 10.17305/bjbms.2021.6606
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the pathological development of dyslipidemia in patients with hypothyroidism

Abstract: According to the previous reports, hypothyroidism has been shown to be strongly correlated with increased circulating concentrations of total cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG). Notably, thyroid hormones  are confirmed to modulate the production, clearance, and transformation process of cholesterol within circulation of mammals. Moreover, emerging evidence suggests that the thyroid-stimulating hormone could also participate in modulating serum lipid metabolism inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 114 publications
(110 reference statements)
0
5
0
4
Order By: Relevance
“…Conducting GO and KEGG pathway analyses on this module unveiled crucial pathways associated with GD pathogenesis. Noteworthy findings encompass heightened DNA binding transcription factor processes, links to conditions like Microcephaly, primary autosomal recessive cataracts, spastic paraparesis, speech delay, and perturbations related to peroxisomal fatty Acyl-Coa reductase disorder [ 48 ]. These insights underscore the potential involvement of these processes in the mechanisms driving GD [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conducting GO and KEGG pathway analyses on this module unveiled crucial pathways associated with GD pathogenesis. Noteworthy findings encompass heightened DNA binding transcription factor processes, links to conditions like Microcephaly, primary autosomal recessive cataracts, spastic paraparesis, speech delay, and perturbations related to peroxisomal fatty Acyl-Coa reductase disorder [ 48 ]. These insights underscore the potential involvement of these processes in the mechanisms driving GD [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…В большинстве случаев врачи различных специальностей (кардиологи, неврологи, участковые терапевты, врачи общей практики) сталкиваются и анализируют уже клинические кардиальные и церебральные исходы и осложнения у пациентов с патологией щитовидной железы, часто рассматривая эндокринную патологию в качестве сопутствующего, но не потенцирующего атерогенез состояния. В отношении стратификации групп кардиоваскулярного и церебрального риска, необходимости выбора сроков начала и способов антиатерогенной терапии у пациентов с различным гормональным статусом щитовидной железы мнения ученых весьма противоречивы [14,[29][30][31][32][33][34][35][36][37][38][39]. Кроме того, в случае подозрения на вторичную гиперлипидемию необходимо учитывать и другие обстоятельства, обусловленные коморбидностью патологии.…”
Section:  вторичная гиперлипидемия и атеросклероз у пациентов с пато...unclassified
“…Некомпенсированный гипотиреоз характеризуется ухудшением качества жизни и серьезными кардиометаболическими нарушениями. Вместе с тем риск развития ССЗ может повышаться и при его субклинической форме [14,[28][29][30][31][32][33][34][35][36][37][38][39]52].…”
Section:  роль гормонов щитовидной железы в развитии гиперлипидемииunclassified
See 1 more Smart Citation
“…Hypothyroidism can be seen in any age group, predominantly in middle-aged and older adults. It can change many metabolic processes in the body (5,6). Although hypothyroidism and severe or prolonged hyperthyroidism can cause hair loss, previous studies have shown that changes in the hair cycle do not cause hair loss in patients with thyroid disorders.…”
Section: Introductionmentioning
confidence: 99%